Leveraging a Virtual Community of Practice to Participate in a Survey‐based Study: A Description of the METRIQ Study Methodology. Issue 2 (22nd March 2017) - Thoma, Brent; Paddock, Mike; Purdy, Eve; Sherbino, Jonathan; Milne, William Ken; Siemens, Marshall; Petrusa, Emil; Chan, Teresa
Abstract: Objectives: To power the METRIQ (Medical Education Translational Resources: Impact and Quality) Study adequately, we aimed to recruit > 200 medical students, residents, and attendings to complete a 90‐ to 120‐minute survey by leveraging a virtual community of practice (vCoP). Methods: Participants were recruited using personal (conference campaign and e‐mails) and online (a study website and social media campaign utilizing Twitter, Facebook, blogs, podcasts, an infographic, and a YouTube video) techniques that leveraged relationships within a virtual community or practice. Participants received weekly survey reminders for 4 weeks and at the end of the rating period. Survey completion rates were calculated. Results: A total of 380 potential participants completed an intake form (139 medical students, 120 residents, 121 attendings), 330 consented to participate, and 309 (81.3% of interested and 93.9% of consenting participants) completed the full survey (121, 88, and 100, respectively). The required sample size was achieved. Conclusions: The METRIQ Study utilized a multimodal recruitment campaign that targeted a vCoP. It recruited large numbers of participants with high completion rates. Response rates could not be calculated given the uncertainty surrounding the number of individuals invited to participate.